1994
DOI: 10.1002/chin.199409202
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Platinum(0)‐Catalyzed Diboration of Alkynes.

Abstract: 1994organo-boron compounds, nonmetal heterocycles organo-boron compounds, nonmetal heterocycles S 0047 -202Platinum(0)-Catalyzed Diboration of Alkynes.-Although solvents do not play an important role in the title reaction yielding the products (III), the addition is apparently accelerated in polar solvents in the order DMF ¿ MeCN ¿ THF ¿ toluene. By boron cross-coupling reaction, the decene (V) is prepared. -(ISHIYAMA, T.; MATSUDA, N.; MIYAURA, N.; SUZUKI, A.;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…These species were, in fact, found to be more active than the initially used catalyst precursor Pt(PPh 3 ) 4 . 313,314 In the same studies, further evidence was gathered that suggested that phosphine dissociation is a key step in the reaction. If a chelating bis-phosphine such as dppe (1,2-bis-(diphenylphosphino)ethane) is used instead of two monodentate phosphine ligands, the platinum complex is found to be catalytically inactive.…”
Section: Mechanistic Studies Of 12-diboration Processesmentioning
confidence: 95%
See 2 more Smart Citations
“…These species were, in fact, found to be more active than the initially used catalyst precursor Pt(PPh 3 ) 4 . 313,314 In the same studies, further evidence was gathered that suggested that phosphine dissociation is a key step in the reaction. If a chelating bis-phosphine such as dppe (1,2-bis-(diphenylphosphino)ethane) is used instead of two monodentate phosphine ligands, the platinum complex is found to be catalytically inactive.…”
Section: Mechanistic Studies Of 12-diboration Processesmentioning
confidence: 95%
“…The first synthetically relevant diboration of both internal and terminal alkynes was reported in 1993 by Miyaura, Suzuki, and co-workers using B 2 pin 2 and a catalytic amount of a platinum(0) complex, typically Pt(PPh 3 ) 4 . 313 Alkenylboron products were generated in high yields (>90%) when reactions were carried out in DMF at 80 °C for 24 h in the presence of 3 mol % of a zerovalent platinum complex. The formation of the cis isomer was established with high selectivity (>99%).…”
Section: Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…Arylboronic acids represent another important class of useful reagents with countless applications in many fields, such as cross-coupling 13−15 (the Suzuki−Miyaura cross-coupling, the Chan−Lam coupling, and the Petasis−Borono Mannich reaction), materials science, 16 and drug discovery. 17 Therefore, substantial efforts have been devoted to their preparation, and several methods have been developed, such as transmetalation from organometallic reagents, 18 Miyaura borylation, 19,20 metalcatalyzed C−H activation, 21 and a SET process. 22−26 In particular, Miyaura borylation is an attractive method among them due to its functional-group compatibility, broad substrate scope, and robustness.…”
mentioning
confidence: 99%
“…DMAP = 4-dimethylaminopyridine; TEA = triethylamine; DBU = 1,8-diazabicyclo [5,4,0] electron-donating effect of the substituent (control experiment, see SI, Table S5). 31 Disubstituted arylalkynes are also suitable substrates for this transformation (18,19), but alkylsubstituted alkynes are not incompatible (20). This transformation will extend the synthetic utility of alkynes as platforms (mechanistic probes, see SI, Scheme S1, Figure S2).…”
mentioning
confidence: 99%